A non-surgical conservative management of congenital dacryostenosis - Srivastava, Namrata; Dwivedi, P. N.; Sadiya, Haleema (International Journal Of Community Medicine And Public Health, 2023)
Background: Congenital canaliculus stenosis often occurs in about 25-30% of all new born. In many cases, a narrowing of the Nasolacrimal duct can be seen due to a persistent of Hasner membrane. Conservative treatment begins with lacrimal sac massage in the first month of life. This study was conducted to determine non-surgical conservative treatment for congenital lacrimal stenosis in infants and young children. Study design: prospective observational study. The settings are the “Satya eye hospital and research institute”, Kanpur UP from December 2015 to October 2017. Methods: Nasal sac massage (Crigler massage) with or without topical antibiotics was recommended for 281 children less than 10 months of age diagnosed with congenital canaliculus stenosis. Resolution of lacrimal stenosis was assessed at 4 and 7 months and was defined as the absence of any clinical signs of NLDO. At 7 months, at visits, 244 eyes (83%) of 281 patients showed conservative treatment. Results: Conservative treatment of CNLD with Crigler massage was successful in most cases treated in 281 (84%) of 335 eyes with congenital canaliculus stenosis. The remaining 54 (16%) eyes were examined. Age (p=0.001) and unilaterality (p=0.001) were found to be associated with the loss of clinical signs. Conclusions: In this study, we conclude that nonsurgical conservative treatment has a high overall success rate for congenital canaliculus stenosis and that this form of treatment can be considered one of the best options in infants and young children.